The Effect of Temperature on Formaldehyde Migration and the Validation of Analytical Methods Used in Herbal Plastic Packaging - Nisma, Fatimah; Riyanti, Hurip Budi; Julanda, Delta (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Plastic as food packaging has been the subject of extensive research, but plastic as packaging for herbs does not yet exist. As an additive, plastic made from the monomer and urea-formaldehyde is utilized. At elevated temperatures, formaldehyde can decompose due to the degradation of the monomer, followed by oxidation and the severing of the carbon chain. Formaldehyde can migrate to the bundled material, which is hazardous to human health. This study aimed to ascertain the impact of temperature on the migration of formaldehyde from plastic used to wrap herbs. The sample is a plastic bag used to wrap herbs, and NIR (Near Infrared) is used to determine the variety of plastic. Formaldehyde migration was determined by heating the sample between 40 and 80 degrees Celsius, and formaldehyde was analyzed using the UV-Vis spectrophotometer method with Nash reagent. The absorbance of formaldehyde was measured with a spectrophotometer at a wavelength of 412 nm. The type of plastic obtained was PP (Poly Propylene). The equation for the formaldehyde calibration curve is y = 0.0197x + 0.1218 with a correlation coefficient (r) of 0.999. The migration of formaldehyde was measured after heating plastic to temperatures between 40 and 80 degrees Celsius. The released formaldehyde concentrations ranged from 7.35 to 13.47 µg/mL. Validation of the analytical method revealed the formaldehyde detection limit (LOD) to be 0.8024 µg/mL and the quantity limit (LOQ) to be 2.6745 µg/mL, with a precision of 1 and an accuracy of 97,462-113,851%, thereby satisfying the meticulous, exhaustive, and precise criteria.